A methodology for the measurement of carbon monoxide concentration during in-situ combustion with tunable diode laser (2016)
A TDL system is reported to monitor carbon monoxide (CO) concentration under conditions similar to those of laboratory-scale tests used to characterize the behaviour of a heavy crude oil during in situ combustion (ISC). The TDL-CO sensor uses a DFB diode laser operating over the spectral range of the rotational transition R(11) of the CO-2v-vibrational band, where simulations of spectral absorption bands for CO, CO2 and H2O show minimal spectral interference. The absorption spectra were calculated using HiTran 2008 Database, under typical conditions of temperature of 150oC to 800oC, pressures from 1 atm to 5 atm and major species compositions observed in ISC characterization experiments. CO-concentration measurements were conducted in a static-glass cell, of Duran R borosilicate glass 3.3 with a pathlength of 3.81cm, to validate the CO sensor architecture under controlled laboratory environments. A calibration curve of CO was obtained by quantifying the optical density at the line center of R(11) for a concentration range between 0:7%mole to 3:4%mole which reached a R-squared of 0.9986. High-pressure and temperature experiments were carried out in a custom-designed combustion chamber with optical access, which has two optical wedged sapphire Windows (2o) to avid etalon effects. CO-absorption spectra were validated by a comparative study with HiTran Database while a free-calibration methodology using scanned-wavelength direct absorption TDL was investigated for future characterizing experiments of ISC. Typical Signal to Noise Ratios (SNRs) were above 40, although for the static glass cell a value of SNR = 14 was observed. The linestrengths for R(11) of _0= 2 _00 = 0 were also measured and validated with HiTran. The calibration experiments showed the potential of 2.3 _m TLD-CO sensor for non-invasive, in-situ combustion monitoring of CO generated at conditions to those of ISC experiments.